2016
DOI: 10.1007/s00702-016-1619-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of various doses of topiramate against methylphenidate-induced oxidative stress and inflammation in isolated rat amygdala: the possible role of CREB/BDNF signaling pathway

Abstract: Methylphenidate (MPH) abuse damages brain cells. The neuroprotective effects of topiramate (TPM) have been reported previously, but its exact mechanism of action still remains unclear. This study investigated the in vivo role of various doses of TPM in the protection of rat amygdala cells against methylphenidate-induced oxidative stress and inflammation. Seventy adult male rats were divided into seven groups. Groups 1 and 2 received normal saline (0.7 ml/rat) and MPH (10 mg/kg), respectively, for 21 days. Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 69 publications
1
39
0
Order By: Relevance
“…To counteract the effects of ROS, there are antioxidant-producing systems including superoxide dismutase (SOD) which is an important antioxidant scavenging free radicals and preventing oxygen toxicity [18]. Interestingly, activation of CREB protects various cell types, including neurons, against ROS-induced damage [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…To counteract the effects of ROS, there are antioxidant-producing systems including superoxide dismutase (SOD) which is an important antioxidant scavenging free radicals and preventing oxygen toxicity [18]. Interestingly, activation of CREB protects various cell types, including neurons, against ROS-induced damage [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Worthy of note is that the hippocampal neurons are particularly sensitive to a variety of excitatory amino-acid mediated cerebral damage. Recent observations of Motaghinejad et al [11][12][13] concerning neuroprotection of topiramate against methylphenidate-induced neurodegeneration in dentate gyrus and CA1 regions of the rat isolated hippocampus [11,13] and also in isolated rat amygdala [12] suggest that this antiepileptic drug can be used as a neuroprotective agent against apoptosis, oxidative stress and neuroinflammation. This could be partly caused by the activation of GABAA receptor, inhibition of AMPA/kainite receptor and probably via CREB/BDNF pathway [11][12][13].…”
Section: Discussionmentioning
confidence: 98%
“…Neurochemical studies suggest that the anticonvulsant and neuroprotective properties of this AED in various experimental models involve its multidirectional effect on the CNS, especially on the hippocampus structure, and are mainly based on the modulation of its GABA-ergic system. This is probably due to the involvement of AMPA/kainate and GABAA receptors, with antagonistic effects of TPM on glutamate receptors of the AMPA/kainate subtype, which play an essential role in excitotoxic neuronal damage [3,5,[11][12][13]17,32]. Worthy of note is that the hippocampal neurons are particularly sensitive to a variety of excitatory amino-acid mediated cerebral damage.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] On the other way, it was suggested that ACE-2 is one of the main enzymes, which by the mediation of some important protein such as Mas protein, regulates normal brain function and release of neurotrophic factors such as brain-derived neurotrophic factor (BDNF)[ 7 8 ] BDNF has a critical role in neurodevelopment, neurogenesis, inhibition of occurrences of neurodegeneration, and normal mood behavior such as mood stability and cognitive function. [ 9 ] According to this concept, it was approved that decrease activity of ACE-2 or reduction of its expression by some natural and acquired accident can disturb normal neurological and mental activity and can remain long term sequels. [ 8 10 11 ] Taken together according to recent studies, it was suggested that ACE-2 can be a target for COVID-19 in a strategic organ such as the brain and based on these data, it can be assumed that infection by COVID-19 may cause inhibition of ACE-2 and its downstream, BDNF, thus, it can instigate neurodegeneration (increase of oxidative stress, neuroinflammation, and apoptosis) and can probably cause mentally related disorders such as anxiety, depression, and cognition impairment.…”
Section: Hypothesismentioning
confidence: 99%